Reconstruction with Total Scapular Reverse Total Shoulder Endoprosthesis after Radical Tumor Excision - Michael J. Harvey; Howard G. Rosenthal (Case Reports in Oncological Medicine)
Malignant musculoskeletal tumors about the shoulder girdle region involving the scapula are fairly rare, but when diagnosed, challenging and complex surgical treatment may be warranted with the primary goal of improving patient survival. These tumors are typically extensive and infiltrative at the time of presentation, requiring radical resection to achieve margins and obtain local tumor control. Historically, forequarter amputation or flail extremity were the mainstays of treatment in these cases. Presently, with recent advances in diagnostics, imaging, adjuvant therapies, and surgical treatment, many patients presenting with malignant tumors involving the scapula are candidates for limb salvage surgery. Reconstruction with endoprosthesis seems to have gained acceptance as the preferred surgical treatment for such lesions, as this intervention has resulted in improved postoperative function and cosmesis, with an acceptable complication rate. We present our experience with recent advancement in these surgical efforts in the form of shoulder girdle reconstruction with total scapular reverse total shoulder prosthesis after radical tumor excision.